An exploratory study using video analysis of rheumatology specialist nurses conducting methotrexate education consultations with patients. (27th February 2021) - Robinson, Sandra; Scott, Jason; Adams, Nicola; Heslop, Peta; Hassell, Andrew; Ryan, Sarah; Walker, David
Abstract: Background: Prior to commencing methotrexate, patients routinely attend an education consultation with a rheumatology nurse. The purpose of the consultation is to discuss the patients' expectations and concerns related to commencing methotrexate, the benefits of treatment, potential side effects and monitoring requirements. The aim of this study was to use video analysis to assess the structure, content and mode of delivery of the consultation. Methods: Video recordings of 10 patient–nurse consultations, involving four specialist rheumatology nurses, were analysed and transcribed. The consultations were compared with the Calgary–Cambridge (CC) consultation model. Transcripts were thematically analysed. Data were quantitatively assessed for verbal and non‐verbal behaviours. Findings: Assessment of the video data using the CC model demonstrated good structure, content and flow of the consultation, influenced by the use of an information leaflet. Consultations generally consisted of communication from nurse to patient rather than a dialogue; the nurse spoke for 69%–86% of the time; clarification of the patient's understanding of the information did not take place in any of the consultations. Thematic analysis also showed that the nurse agenda dominated and the nurse was aware of 'overloading' the patient with information. Cues from the patients to discuss items of importance were often missed. Conclusion: Video analysis can be used to identify the aspects of the consultation that work well and those areas of the consultation that could be improved with specific training.